Optimisation of Concentration of Undaria pinnarifida (Wakame) and Himathalia elongate (Sea Spaghetti) Varieties to Effect Digestibility, Texture and Consumer Attribute Preference. Issue 8 (14th September 2021) - Wilkin, Jonathan D.; Ross, Katrina; Alric, Tiffany; Hooper, Matthew; Grigor, John V.; Chu, Boon-Seang
ABSTRACT: In this study, seaweed concertation in a model system (cracker) was investigated to better understand addition of seaweed on starch modulation, texture, and consumer attribute detection. Temporal dominance of sensations (TDS) showed that seaweed concentrations over 15% had a dominant attribute of fishy for both Wakame and Sea Spaghetti varieties, whereas for both, Crunchy was observed for the 5% and 10% crackers. This corralled well with the texture analysis where crackers fortified with both seaweeds at 5% and 10% have a harder texture, with lower fracturability compared to higher concentrated seaweed crackers. The fracturability levels within the 15% and 20% crackers were comparable to the no substitution controls. In vitro digestion indicated that glucose was liberated immediately after initiation, with both seaweed systems reaching plateau by 4 minutes. In this study it was observed that seaweed variety affected starch digestibility, with wakame seaweed inhibiting starch digestion.